Epistemologi Ilmu Ibnu Rusyd dan Implikasinya terhadap Pendidikan Pesantren - Arbain Arbain; Wildan Rifqi Asyfia; Nurul Mubin (Reflection : Islamic Education Journal, 2026)
The concept of science according to Ibn Rushd emphasizes the harmony between religion and philosophy, as well as the importance of using rational thinking methods to achieve the truth. He divides human intellectual abilities into three levels, namely rhetoric, dialectical, and demonstrative, and distinguishes science into theoretical and practical sciences. According to Ibn Rushd, knowledge is obtained through cooperation between the senses, imagination, and intellect, so that the human thought process must run systematically and logically. This research uses the library research method to examine the relevance of Ibn Rushd's thought to Islamic boarding school education in the modern era. The results of the study show that Ibn Rushd's ideas can be the basis for integration between religious science and science, encourage the strengthening of students' critical reasoning, and avoid scientific dichotomy. In addition, the application of his thinking has the potential to improve the quality of learning for Islamic boarding schools to be more contextual, inclusive, and adaptive to the development of science and technology. Thus, the concept of Ibn Rushd's knowledge can strengthen the direction of pesantren education towards a holistic and civilization-oriented education system.